THE EFFORTS TO DEVELOPMENT OF BUSINESS INNOVATION BY MICRO SMALL AND MEDIUM (MSMES) THE TASTY CAKE MBAK YUL IN PANDEGLANG BANTEN - Raden Irna Afriani; Yuliah Yuliah; Hafidz Hanafiah; Ihwan Satria Lesmana; Khaeruman Khaeruman; Ina Khodijah; Mochamad Fahru Komarudin (International Journal of Engagement and Empowerment, 2023)
Micro, Small and Medium Enterprises (MSMEs) are businesses that have a small scale with a limited number of employees and relatively low turnover. MSMEs are often owned and run by the owners themselves or on a family scale. The decline in consumer purchasing power is a major challenge for MSME players. However, online sales can be an opportunity to survive this pandemic. Considering that there are still many MSMEs who do not understand online sales, empowering them to try online markets and to compare superior products is very important. By using and managing the right digital media, economic actors should be able to increase public interest in their products. The approach used in this community service, namely direct assistance to the field in developing MSME business innovation, is a very effective step to increase brand awareness and assist business actors in developing offline marketing strategies. Several points that can be applied in this approach, namely: innovation development, offline promotion: direct assistance, sharing best practices, evaluation and follow-up support. The MSME assistance activity at the Kue Enak location, Pandeglang Regency, Banten Province consists of several stages involving interviews with business owners and the community service team. The steps that can be followed in this mentoring process are: Interviews with Business Owners, Making Snack Box Orders, Making Banners and Price Tags, Training on Marketing and Branding, Evaluation and Follow Up. Through this assistance, it is hoped that Cake Delicious business owners can increase public interest in their products, strengthen brand awareness, and maximize sales opportunities online and offline